Diffuse infantile hepatic haemangioma—how to manage an incidental but potentially lethal finding. Issue 8 (21st August 2018) - Rodrigues, Alexandra; Forno, Andreia; Costa, Edite; Berenguer, Alberto; Pilar, Carla; Loureiro, Rui; Rufino, Duarte; Barros, Andreia; Teixeira, Filomena
Abstract: Infantile hepatic haemangioma (IHH) is a rare vascular tumour that is potentially lethal due to its associated complications, including heart failure, hepatic failure, hypothyroidism and abdominal compartment syndrome. The authors report a case of an asymptomatic diffuse IHH in a newborn male, which was presented as an incidental finding at the time that the patient was diagnosed with pyloric stenosis. The patient was treated with increasing doses of propranolol that were well tolerated. With the regression of the IHH by the time that the patient reached one year of age, there was a significant imagiologic improvement. Because there is no consensus on the optimal approach for the treatment of liver tumours in newborns, it is important to adopt a systematic approach. After the diagnosis of diffuse IHH has been established, the decision to initiate treatment and the therapeutic of choice is often controversial. Regular follow-up is recommended to monitor possible complications.